Exploring the application of a self-determined approach to learning. (2017) - Snowden, Michael; Halsall, Jamie P.
University education has traditionally been seen as a dyadic relationship between the lecturer and the learner: typically, it is the lecturer who decides what the learner needs to know in terms of knowledge and skills, and indeed, how the knowledge and skills should be taught. The aim of this paper is to critically explore the contemporary debates on the application of self-determined learning within a higher education setting. This research project used a series of qualitative focus group meetings. This research recommends that there is a need for a clearer requirement for on applying heutagogical principles for promoting engagement in the higher education teaching and learning environment.